0
$\begingroup$

I'm facing a bit of trouble figuring out this limit.

$$ \lim_{n \to \infty} \cos\left(\left(-1\right)^n \frac{n-1}{n+1}\pi\right)$$

and I'm not sure if I can simply find the limit of the inner functions and then apply cosine to that, as in $$ \lim_{n \to \infty} (-1)^n = undefined \quad \quad \lim_{n \to \infty} \frac{n-1}{n+1} = 1 \quad \quad \lim_{n \to \infty} \pi = \pi $$ But because of the oscillation caused by $\displaystyle\lim_{n \to \infty} (-1)^n$, I am not sure what I should do. It would seem to me that the entire thing is undefined, but that is a bad answer.

$\endgroup$
  • $\begingroup$ $n\to\infty$ does not necessarily imply $n$ is an integer, for non integer $n,(-1)^n=?$ $\endgroup$ – lab bhattacharjee Apr 28 '18 at 18:11
  • $\begingroup$ True. Then it would tend to oscillate. I'm not quite sure what I can do with that then. Thanks $\endgroup$ – user25758 Apr 28 '18 at 18:20
  • $\begingroup$ Usually $n$ is used to denote an integer, so assuming it is, note that $\cos(-\pi)=\cos(\pi)=-1$. $\endgroup$ – Cedron Dawg Apr 28 '18 at 19:06
1
$\begingroup$

Note that $\cos$ is even; that is, $\cos(x)=\cos(-x)$ for any $x\in\mathbb{R}$. Thus,

  • If $n$ is odd, then $\cos\left((-1)^n \frac{n-1}{n+1}\pi\right)=\cos\left((-1)^{n+1}\frac{n-1}{n+1}\pi\right)=\cos\left(\frac{n-1}{n+1}\pi\right)$.
  • If $n$ is even, then $\cos\left((-1)^n \frac{n-1}{n+1}\pi\right)=\cos\left(\frac{n-1}{n+1}\pi\right)$.

Therefore, $$\lim_{n\to\infty}\cos\left((-1)^n \frac{n-1}{n+1}\pi\right)=\lim_{n\to\infty}\cos\left(\frac{n-1}{n+1}\pi\right)=\cos\pi=-1.$$

$\endgroup$
  • $\begingroup$ Simple and clear explanation +1 $\endgroup$ – Paramanand Singh Dec 22 '18 at 7:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.